Macroalgal biomass as a potential resource for lactic acid fermentation. (December 2022) - Nagarajan, Dillirani; Chen, Chun-Yen; Ariyadasa, Thilini U.; Lee, Duu-Jong; Chang, Jo-Shu
Abstract: Lactic acid is an essential platform chemical with various applications in the chemicals, food, pharmaceutical, and cosmetic industries. Currently, the demand for lactic acid is driven by the role of lactic acid as the starting material for the production of bioplastic polylactide. Microbial fermentation for lactic acid production is favored due to the production of enantiomerically pure lactic acid required for polylactide synthesis, as opposed to the racemic mixture obtained via chemical synthesis. The utilization of first-generation feedstock for commercial lactic acid production is challenged by feedstock costs and sustainability issues. Macroalgae are photosynthetic benthic aquatic plants that contribute tremendously towards carbon capture with subsequent carbon-rich biomass production. Macroalgae are commercially cultivated to extract hydrocolloids, and recent studies have focused on applying biomass as a fermentation feedstock. This review provides comprehensive information on the design and development of sustainable and cost-effective, algae-based lactic acid production. The central carbon regulation in lactic acid bacteria and the metabolism of seaweed-derived sugars are described. An exhaustive compilation of lactic acid fermentation of macroalgae hydrolysates revealed that lactic acid bacteria can effectively ferment the mixture of sugars present in the hydrolysate with comparable yields. The environmental impacts and economic prospects of macroalgal lactic acid are analyzed. Valorization of the vast amounts of spent macroalgal biomass residue post hydrocolloid extraction in a biorefinery is a viable strategy for cost-effective lactic acid production. Graphical abstract: Image 1 Highlights: Macroalgal biomass is a potential sustainable feedstock for lactic acid production. Green, red and brown macroalgal biomass have been fermented to lactic acid. Macroalgal cultivation and processing has the highest environmental impacts. Metabolism of non-fermentable macroalgal carbohydrates is a major bottleneck. Integrated macroalgal biorefinery for lactic acid production is economically viable.